Rational peptide selection to detect human immunodeficiency virus type 1-specific T-cell responses under resource-limited conditions. - Willberg, C; Pillai, S; Sharp, E; Rosenberg, MG; Agudelo, J; Barbour, J; Nixon, D (2007)
Understanding human immunodeficiency virus type 1 (HIV-1)-specific cytotoxic T-lymphocyte responses is important for the development of vaccines and therapies. We describe a novel method for the rational selection of peptides that target stable regions of the HIV-1 genome, rich in epitopes specifically recognized by the study population. This method will be of particular use under resource/sample-limited conditions.